Peran PERAN DINAS SOSIAL KABUPATEN PANDEGLANG DALAM PEMBERDAYAAN MASYARAKAT MELALUI PKH (PROGRAM KELUARGA HARAPAN) DI KELURAHAN KADUMERAK TAHUN 2022 - Ade Millatus Sa'adiyyah; Nina Mulyasari (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
Overty is a phenomenon and social problem and it is continuously studied and concern to the central government and regional governments. This study aims to find out the activities of the Pandeglang Regency Social Service in community empowerment through PKH (Program Keluarga Harapan) and to find out what efforts have been made by the Pandeglang Regency Social Service through PKH (Program Keluarga Harapan) in Kadumerak Village in 2022. Research methods used is a qualitative descriptive research method. The source of data in this qualitative research is to dig up information directly from sources of information that are considered related to community empowerment through PKH (Program keluarga harapan) in Kadumerak Village in 2022. As for the informant in this study is the Head of Social Protection and Security, Head of Social Welfare Section, PKH Facilitator, and KPM PKH Participant. The results of this study indicate that the implementation of PKH and the role of the Pandeglang District Social Service through PKH (Family Hope Program) in Kadumerak Village in 2022 is in accordance with its objectives, namely to provide health services, education and improve social welfare to very poor groups of people. The Pandeglang district social service experienced several obstacles, including data that was out of sync between KPM PKH participants and the original situation on the ground, and the length of time for updating data made it difficult for the Pandeglang District Social Service to enter data on new PKH participant candidates. Then there is a lack of public understanding regarding the PKH program. The efforts of the Pandeglang Regency Social Service in empowering the community through PKH (Family Hope Program) in 2022 are to improve the quality of information center services regarding PKH complaints and socialization by taking an outreach approach with the community regarding PKH (Family Hope Program). Keywords: Role of Social Services, Community Empowerment, Family Hope Program.